2021
DOI: 10.1016/j.scitotenv.2021.148129
|View full text |Cite
|
Sign up to set email alerts
|

Environmental impacts of COVID-19 treatment: Toxicological evaluation of azithromycin and hydroxychloroquine in adult zebrafish

Abstract: One of the most impact issues in recent years refers to the COVID-19 pandemic, the consequences of which thousands of deaths recorded worldwide, are still inferior understood. Its impacts on the environment and aquatic biota constitute a fertile field of investigation. Thus, to predict the impact of the indiscriminate use of azithromycin (AZT) and hydroxychloroquine (HCQ) in this pandemic context, we aim to assess their toxicological risks when isolated or in combination, using zebrafish ( Danio re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 120 publications
0
14
0
Order By: Relevance
“…6 and Supplementary Table 5 ). A previous study demonstrated enhancement of the oxidative stress processes in zebrafish because of HCQ exposure 13 . We found two genes, namely nfe2 and pxdn, that are involved in the oxidative stress process.…”
Section: Resultsmentioning
confidence: 95%
“…6 and Supplementary Table 5 ). A previous study demonstrated enhancement of the oxidative stress processes in zebrafish because of HCQ exposure 13 . We found two genes, namely nfe2 and pxdn, that are involved in the oxidative stress process.…”
Section: Resultsmentioning
confidence: 95%
“…Hydroxychloroquine, approved by the Food and Drug Administration (FDA) as an antimalarial drug, was reused to treat COVID-19 patients (da Luz et al, 2021;Mendonça-Gomes et al, 2021). Cell culture experiments have shown solid antiviral action of hydroxychloroquine against a variety of viruses, including HIV-1, dengue, Zika and West Nile viruses, Venezuelan equine encephalitis virus, Chikungunya, pseudorabies virus, adenovirus, and SARS-CoV-2 (COVID-19) (Gautret et al, 2021;Jans and Wagstaff 2021), in dermatology and rheumatology and emerging roles in oncology (Yusuf et al, 2017).…”
Section: Hydroxychloroquinementioning
confidence: 99%
“…The presence of azithromycin and hydroxychloroquine at 12.5 μg/L affects wild aquatic life, such as neotropical tadpoles of Physalaemus cuvieri species. In fishes like Zebrafish (Danio rerio), azithromycin and hydroxychloroquine at 2.5 μg/L induce protein reduction, redox imbalance, and possible oxidative stress (Mendonça-Gomes et al, 2021). In the European Sea, Bass (Dicentrarchus labrax) azithromycin causes oxidative stress, peroxidative damage and neurotoxicity at 20 mg/L, inducing 18% and 7.5% of larvae mortality and morphological abnormalities, respectively (Mhadhbi et al, 2020).…”
Section: Toxicity To Aquatic Organismsmentioning
confidence: 99%
See 1 more Smart Citation
“…This antibiotic was previously proved to induce both chronic and acute toxic effects on wildlife, including the marine biota ( Shiogiri et al, 2017 ). Indeed, the toxicity of azythromycin was investigated by experiments carried mainly on fish species such as the Chinook salmon Oncorhynchus tshawytscha ( Fairgrieve et al, 2005 ), the tilapia Oreochromis niloticus ( Shiogiri et al, 2017 ), and the zebrafish Danio rerio ( Mendonça-Gomes et al, 2021 ). The results found supported diverse physiological effects and a reduction in total protein levels.…”
Section: Introductionmentioning
confidence: 99%